The Decriminalization of Abortion in Latin America. A Tale of Gradual Judicialization - Díez, Jordi (2024)
In the context of the Green Wave, three Latin American countries recently have amply decriminalized access to abortion: Mexico (2021, 2023), Colombia (2022), and Argentina (2020) (Uruguay did so in 2012). The recent wave of decriminalization is the culmination of larger, historical processes that involved the gradual judicialization of reproductive rights in the region. Courts have been a central part of the story. In these three cases, arguments advanced by state and nonstate actors in favor of decriminalization significantly built on jurisprudence developed over many years. This article explains that the process of abortion decriminalization has been partly a tale of gradual judicialization.